Nadzom Method Implementation in Arabic Language Learning at DTA Ar-Risalah Pangandaran (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The Real Work Lecture Programme at DTA Al Risalah Pangandaran uses the Nadzom technique to teach Arabic language acquisition. Studies have focused on humans since they are distinct and varied social animals in many domains, including language. Arabic, a multilingual tongue, is essential to Muslims for religious and communicational purposes. Arabic language education is crucial for giving kids a strong foundation, especially in their early years. The Nadzom method—which includes activities including material preparation, song selection, Arabic language instruction, voice training, group exercises, discussion sessions, and performances—is used to approach this learning. Children will be able to comprehend and use Arabic in their daily lives thanks to this learning technique.